Analisis Pengaruh Brand Awareness, Brand Loyalty dan Harga terhadap Kepuasan Pelanggan PT. Jico Agung Jakarta - Estu Mahanani; Bida Sari (Sekolah Tinggi Ilmu Ekonomi Indonesia (STEI) Jakarta, 2019)
This study aims to determine the effect of brand awareness (X1), brand loyalty (X2) and price (X3) on Customer Satisfaction (Y). The method used is the interactive-associative research. This research population is all of the PT. Jico Agung’s customer in East Jakarta. The sampling technique is done by purposive sampling with certain criteria. The sample of the research are 30 respondents (PT. Jico Agung’s customer who live in RT.013 and 014, RW.07, North Utan Kayu, East Jakarta. Data collection is using observation, interviews and questionnaires. Analysis of the data used is quantitative analysis, including correlation analysis, determination analysis and multiple linear regression analysis (simultaneously), and hypothesis testing using t-test and F-test. The results of data processing performed with SPSS 25.0 for windows. The value of correlation coefficient (R) is 0,848. The value of determination coefficient (R2) is 0,687. It means that 68,7% variation of dependent variable (Customer Satisfaction) could be predicted from the combination of variables (brand awareness, brand loyalty and price) and the remaining 31,3% is influenced by other factors. The regression equation was obtained Ŷ = 0,26 + 0,360 X1+ 0,397X2 + 0,234X3. For the F test obtained F value is calculated at 22.266, greater than F-table (2,98) with α = 5%, so the conclusion: reject Ho and Ha is accepted. It means there is significant influence of brand awareness (X1), brand loyalty (X2) and price (X3) together on Customer Satisfaction (Y).